(untitled) (Andamios, Revista de Investigación Social, 2013)
Research on personal networks has contributed —in the last three decades— collecting information omitted so far in applied research in social science. However, such systematic measurements of interpersonal ties have often exhausted their efforts in the search for their new entities —the networks—, giving little priority to the construction of knowledge from existing social theory. This article revisits notions of Pierre Bourdieu, Erving Goffman and Norbert Elias with the purpose of reducing this gap, looking to bring the initiative of personal networks back to the broader social theory debate.